Monitoring Kelembaban, Suhu, Intensitas Cahaya Pada Tanaman Anggrek Menggunakan ESP8266 Dan Arduino Nano - Reza Akhmad Najikh; Mochamad Hannats Hanafi Ichsan; Wijaya Kurniawan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Orchid is one of the most favored plants. Orchid is one of the most widely exported ornamental plants in Indonesia. In the cultivation of orchids, monitoring the state of the plant is important. Parameters - parameters that need to be monitored include: humidity, temperature, and light intensity. These parameters greatly affect plant growth. Plants can grow well if moisture, temperature, light intensity are well . A good orchid moisture ranges from 60 - 80%. Humidity should not be too high during the night and should not be too low during the day. In addition to humidity, the temperature of the orchid plants should be in the range. The ideal temperature for orchids is: daytime temperature between 27-30 degrees Celsius and night temperature between 21-24 degrees Celsius. Based on these problems, the Moisture Monitoring System, Temperature, Light Intensity on Orchid Plant using ESP8266 and Arduino Nano are designed. In this design, the result of sensor readings will be displayed in graphical form and Chart on IoT Thingsboard. To reading moisture, temperature, light intensity used several sensors they are: LDR, Soil Sensor and DHT-11. From the results of implementation and testing can be concluded that this system can display all the readings of the sensor, and run the system automatically well. The average execution delay is 0.622 seconds and delivery delay is 1.468 seconds.